Selective Infiltration in Polymer Hybrid Thin Films as a Gas-Encapsulation Layer for Stretchable Electronics - Park, Jinseon; Yoon, Hong Rho; Khan, M. Alam; Cho, Sangho; Sung, Myung Mo (American Chemical Society, 2020)
The infiltration depth and water vapor transmission rate (WVTR) were explored in a variety of Al2O3-polymer hybrid layers as thin gas barrier films by filling the free volumes of polymers in the subsurface region with Al2O3 using the atomic layer infiltration (ALI) method. Among all, the prepared Al2O3 - polyethylene terephthalate (PET), Al2O3-polyimide, and Al2O3-Nylon 6 hybrid thin layers with the infiltration depth in the nanometer ranges showed extremely low WVTR values (<10(-6) g m(-2) day(-1)) in a Ca dot corrosion test. Furthermore, we observed selective infiltration among the two polymers [perfluoroalkoxy alkane (PFA) and PET] by a preferential growth of Al2O3 in the PET polymer that might be based on effective functional group anchoring in the ALI process. Then, we demonstrated a novel strategy by employing such a selective infiltration procedure and encapsulating individual segments of 144 Ca dots by Al2O3-PET hybrid thin films on the PFA polymer substrate rather than wrapping the whole thing together for the stretchable gas-encapsulation film. Regardless of stretching, it showed an extremely low WVTR (<10(-7) g m(-2) day(-1)) and is proposed as a highly promising hermetic sealing alternative in stretchable, flexible, and foldable electronic display technologies.
Keywords: LIGHT-EMITTING DEVICES; BARRIER PROPERTIES; PERMEATION; DEPOSITION; VAPOR; TRANSPARENT; AL2O3; PERMEABILITY; DEGRADATION; MECHANISMS